Implementasi Algoritma Rabin Karp Untuk Mendeteksi Kemiripan Dokumen Stmik Bandung - Siti Yuliyanti; Rizky (Jurnal Bangkit Indonesia, 2020)
Document is a form that can be used as proof tool, as the work that has been made, the future of digital documents are vulnerable to the copying of documents directly among the civitas academy, because of the easy access to obtain documents, similarities Document is one of the alternatives that can be used to identify cribbing in the document. similarity is stealing the work of others and admits it as a work of its own, without including references to the original source. Rabin Karp algorithm is a data digging algorithm in the search for text patterns, this algorithm can help search similarity of documents with the application of Rolling Hash method using k-gram, text mining (case folding, tokenizing, filtering, stemming ) and the calculation of the similarity value (dice’s similarity coefficient’s, modulus).